Cambridge Essential English Dictionary The best start to learning english - Walter, Elisabeth; Woodford, Kate (Cambridge Cambridge University press, 2004)
Easy explanations of words, using simple laguage. Helpful: thousands of short, clear examples show you how to use words. 5 pages of the most important phrasal verbs for you to learn.
Contents.
Keywords: Dictionary; English - English